Sustainable water resources management in the Tiber River basin (central Italy) - Calenda, Guido; Mancini, Corrado Paolo (Italian journal of engineering geology and environment, 2009)
The study for the evaluation of the water resource still available in the basin of the Tiber River involved a thorough check of flow observation series, that resulted in a careful revision of stage-discharge relationships and the utilisation of a large amount of stream and spring flow measurements by other sources, in order to interpolate the information obtained in the flow measurement stations.The study was developed in three phases. First, the estimate of the distribution of natural low flow discharges throughout the basin; second, the determination of the minimum instream flow for ecological and other requirements; third, the development of a model that, taking into account the instream flow and present uses of the resources, could evaluate the residual resource still available for further uses and assess the reduction of water consumption aimed at a rational reallocation of water resources.